A Longitudinal Qualitative Analysis of the Lived Experience of the Recovery Process in Opioid-Dependent Patients Post-Detoxification. Issue 3 (27th May 2018) - Ivers, J. H.; Larkan, F.; Barry, J.
ABSTRACT: The aim of the study was to gain an in-depth understanding of opioid-dependent patients' lived experiences post-detoxification. Method : The study employed a naturalistic, observational longitudinal design, involving baseline screening and tracking of patients post-detoxification, with follow-up interviews at three, six, and nine months to observe specific processes of interest. This in-depth investigation of patients at four points was new within an Irish context and novel throughout the literature. Findings : Recovery was seen as a process that was not always linear, and lapse and relapse were viewed as part of this process. Patients had great insight into "risk factors for relapse, " information and knowledge gained over several years and many treatment episodes. Furthermore, the findings illustrate the role insight plays in any learning and growth experience and the emphasis that is placed upon it within the treatment journey; insight is a fundamental underpinning to any real growth and development. The current article argues that insight merits a more explicit role in the model of recovery capital.